Long-term impact of railway transport on morphological development of the largest urban agglomerations in Poland - Jurkowski Wojciech; Kryczka Piotr; Figlus Tomasz; Lisowska-Kierepka Agnieszka; Musiaka Łukasz; Sikorski Dominik; Spórna Tomasz; Sudra Paweł; Szmytkie Robert (Moravian Geographical Reports)
Railway transport accessibility is widely recognized as one of the key factors stimulating spatial development. This dependency was particularly evident during periods of its greatest significance before the era of mass motorization. Despite growing research interest in the issue of relationship between transport and land use, few studies have considered this subject in long-term perspective and in quantitative terms. The primary objective of this study is to determine historical, long-term impact of railway transport on the dynamics of morphological changes in the settlement network. This study was conducted in the eight largest urban agglomerations in Poland, serving as an example of the Central and Eastern European region. The general temporal scope of the study spans the period from 1842 to 1989. The research revealed a strong correlation between railway transport and morphological changes in analyzed urban agglomerations. The most significant changes observed within 1,600 meters of railway stations and up to 20 kilometers from central stations. This quantitative analysis contributed to understanding the long-term impact of railways on spatial development, offering valuable insights for planning and policymaking. The research emphasized the importance of historical context in comprehending current spatial processes, particularly in the context of new railway investments.